Comparison of Motor Skills in Boys and Girls First Grade Student in Tehran - Sepideh Nazi; Sorayya Rahimzadeh-Rahbar; Hossein Karimi (University of Social Welfare and Rehabilitation Sciences, 2006)
Objective: The purpose of this study was to determine the motor skills differences between girls and boys (aged 7) in Tehran in 2004. Materials & Methods: This research was analytical descriptive The subjects were 120 children includes 60 girls and 60 boys. those were selected by simple random sampling at the first grade of primary School. Each subject was individually assessed by Lincoln Oseretsky motor developmental scale. Results: The findings of this research after data analysis by spss soft ware and sample t Test indicated that: There is not any significant differences between total score of motor skills, total balance score, static and dynamic balance with open eyes, bilateral motor coordination, upper limbs coordination, upper and lower limbs coordination, velocity and dexterity of hand movements in boys and girls (P>0/005). The only Significant differences between boys and girls motor skills is eye hand coordination (P<0/03). Conclusion: The findings of this research is used to better planning and defining the theraputic and educational programs in the field of motor development.